Performance Indicators Analysis of Universities Participating in the Priority 2030 Program Research Track - A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev (Высшее образование в России)
The article presents the results of performance indicators analysis of groups of universities participating in “Leadership in Research” track (hereinafter referred to as the research track) of the strategic academic leadership program Priority 2030. To solve this problem, the displaced ideal method was used, which allows to compare the aggregated performance indicators of three groups of universities. The comparative analysis of the special part performance indicators was carried out and also included aggregated indicators of basic and special parts in 2022. To assess the dynamics of universities’ activities in 2020–2022, aggregated indicators of the special part were analyzed. The research showed that special part performance indicators achieved by universities participating in the Program correspond quite well with the results of the general assessment, accepted by the Council at the end of 2023. It was found that the achievement of performance indicators for universities in implementing their development programs had a significant impact on the positions of participants in the research track and enabled the rotation mechanism to be launched in full power for the first time since the beginning of the Program. As a result, 30% of universities in the research track changed their groups